2019
DOI: 10.1016/j.stemcr.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Brain Endothelium Exhibits Stable, Long-Term Barrier Function in Perfused Hydrogel Scaffolds

Abstract: Summary There is a profound need for functional, biomimetic in vitro tissue constructs of the human blood-brain barrier and neurovascular unit (NVU) to model diseases and identify therapeutic interventions. Here, we show that induced pluripotent stem cell (iPSC)-derived human brain microvascular endothelial cells (BMECs) exhibit robust barrier functionality when cultured in 3D channels within gelatin hydrogels. We determined that BMECs cultured in 3D under perfusion conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 59 publications
3
67
2
Order By: Relevance
“…Finally, physiological fluid flow, which is capable of inducing BBB phenotype, suppressing inflammatory signaling, and improving the tightness of the BMEC barrier [11], was added to the system to determine whether culture on LN 511-E8 could improve the ability of iBMECs to demonstrate physiological responsiveness to shear stress. Other studies have reported iBMECs do not show morphological changes or alterations in junctional protein expression due to shear stress on CN IV-FN [15,92,93]. In contrast, we showed that applying shear stress to iBMECs cultured on LN 511-E8, which strongly interacts with β1 integrins, can result in morphological changes and enhanced junctional association of VE-cadherin, claudin-5, and ZO-1.…”
Section: Discussioncontrasting
confidence: 68%
“…Finally, physiological fluid flow, which is capable of inducing BBB phenotype, suppressing inflammatory signaling, and improving the tightness of the BMEC barrier [11], was added to the system to determine whether culture on LN 511-E8 could improve the ability of iBMECs to demonstrate physiological responsiveness to shear stress. Other studies have reported iBMECs do not show morphological changes or alterations in junctional protein expression due to shear stress on CN IV-FN [15,92,93]. In contrast, we showed that applying shear stress to iBMECs cultured on LN 511-E8, which strongly interacts with β1 integrins, can result in morphological changes and enhanced junctional association of VE-cadherin, claudin-5, and ZO-1.…”
Section: Discussioncontrasting
confidence: 68%
“…Most relevant to this commentary, induction and maintenance of endothelial character with a corresponding reduction of epithelial character continues to be a goal. Factors such as hypoxia [19], shear stress [9,19], and three dimensional architecture [10,28,29] have been suggested to increase vascular character, and other models based on induction of BBB character in generic hiPSC-derived ECs are beginning to emerge [32]. Despite these advances, we believe it is prudent to exercise caution when utilizing hPSC-derived BMEC-like cells for studies where the endothelial phenotype is crucial.…”
Section: Main Textmentioning
confidence: 99%
“…We have observed VEGF-dependent network formation in hPSC-derived BMECs using in vitro Matrigel assays [ 1 ], and VEGF has been shown to regulate PLVAP expression in a three-dimensional BBB model that contains hPSC-derived BMECs [ 10 ]. hPSC-derived BMECs also respond to shear; we have observed sprouting-like behavior after culturing these cells in engineered hydrogel matrices under constant perfusion [ 28 ], and others have observed similar phenotypes in hydrogels in response to growth factors and other stimuli such as oxidative stress [ 29 ]. In addition, application of shear after differentiation also led to activation of cholesterol metabolism, proliferation, and angiogenesis transcriptional pathways compared to static controls [ 9 ].…”
Section: Main Textmentioning
confidence: 99%
“…The iPSC-derived BMECs, have well-developed tight junctions, express key BBB markers and, most importantly for the application described here, are a reasonable facsimile of both primary human BMECs and acutely isolated human BMECs in terms of their transporter expression profiles. [17][18][19][20] While several iPSC-derived BBB models with sufficient barrier function are available, [21][22][23][24][25] they have not been employed for identification of new BBB penetrating antibodies. Thus, we used iPSC-derived BMECs to perform a transcytosis screen with a phage display scFv library and identified a cohort of antibodies able to react with human BBB antigens and target the murine brain vasculature in vivo.…”
Section: Introductionmentioning
confidence: 99%